Tissue sensitivity to thyroid hormones may change over time - Giorgio Radetti; Franco Rigon; Alessandro Salvatoni; Irene Campi; Tiziana De Filippis; Valentina Cirello; Silvia Longhi; Fabiana Guizzardi; Marco Bonomi; Luca Persani (European Thyroid Journal, 2023)
Introduction: Patients with congenital hypothyroidism (CH) may transiently show a certain degree of pituitary resistance to levothyroxine (LT4) which, however, normalizes subsequently. However, in some individuals, thyroid-stimulating hormone (TSH) fails to normalize despite adequate LT4 treatment. Methods: Nine patients with CH followed in three Academic Centre who developed over time resistance to thyroid hormones underwent extensive biochemical and genetic analyses. These latter were performed by Sanger sequence or targeted next-generation sequencing technique including a panel of candidate genes involved in thyroid hormone actions and congenital hypothyroidism (CH): THRA, THRB, DIO1, DIO2, SLC16A2, SECISBP2, DUOX2, DUOXA2, FOXE1, GLIS3, IYD, JAG1, NKX2-1, NKX2-5, PAX8, SLC26A4, SLC5A5, TG, TPO, TSHR. Results: All patients displayed a normal sensitivity to thyroid hormone (TH) in the first years of life but developed variable degrees of resistance to LT4 treatment at later stages. In all cases, TSH normalized only in the presence of high free thyroxine levels. Tri-iodothyronine suppression test followed by thyrotrophin-releasing hormone stimulation was performed in two cases and was compatible with central resistance to THs. This biochemical feature was present independently on the cause of CH, being observed either in patients with an ectopic (n = 2) or eutopic gland (n = 3) or in case of athyreosis (n = 1). None of the patients had genetic variants in genes involve d in the regulation of TH actions, while in two cases, we found two double heterozygous missense variants in TSHR and GLIS3 or in DUOX2 and SLC26A4 genes, respectively. Conclusions: We report CH patients who showed an acquired and unexplainable pituitary refractoriness to TH action.